PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI PENGGUNAAN PETA KONSEP PADA SISWA KELAS XII ILMU ALAM SMA NEGERI 1 TELLU LIMPOE PADA TAHUN PELAJARAN 2007/2008 - Akmal, . (bionature, 2008)
The research is intended to know the improvement of the activity and achievement in learning biology at the third year students of science class at SMA Negeri 1 Tellu  Limpoe in  the academic year 2007/2008 on the concept of Growing and Developing through the application of Mind Mapping Approach. The Class Action Research was held on July to October 2008 to 40 third year students of  Science Class at SMA 1 Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang. The data were collected by applying written test to measure the learning achievement and observation sheet to recognize the students activities in learning biology. Based on the data analysis it was concluded that the activity of the students got improvement when using the approach of mind mapping in learning the concept of Growing and Developing . It showed that there was improvement  from 72,12 % (good category)  in the first circle to 80,08% (very good category) in the second circle. The   improvement was also found on the students means score of the post test   from 78,4% in the first circle to 82,2% in second circle after applying the mind mapping approach at the same concept. Keywords : concept map, students activity, learning achievement